A signature pattern of cortical atrophy in dementia with Lewy bodies: A study on 333 patients from the European DLB consortium. Issue 3 (12th November 2018) - Oppedal, Ketil; Ferreira, Daniel; Cavallin, Lena; Lemstra, Afina W.; ten Kate, Mara; Padovani, Alessandro; Rektorova, Irena; Bonanni, Laura; Wahlund, Lars‐Olof; Engedal, Knut; Nobili, Flavio; Kramberger, Milica; et al.
Abstract: Introduction: We explored regional brain atrophy patterns and their clinical correlates in dementia with Lewy bodies (DLB). Methods: In this multicentre study, we included a total of 333 patients with DLB, 352 patients with Alzheimer's disease (AD), and 233 normal controls and used medial temporal lobe atrophy, posterior atrophy, and frontal atrophy (GCA‐F) visual rating scales. Patients were classified according to four atrophy patterns. Results: Patients with DLB had higher scores on all the three atrophy scales than normal controls but had less medial temporal lobe atrophy than those with AD (all P values < .001). A signature hippocampal‐sparing pattern of regional atrophy was observed in DLB. The magnetic resonance imaging measures showed 65% ability to discriminate between DLB and AD and marginally contributed to the discrimination over and above the core clinical features. Discussion: The most common pattern of atrophy of DLB was hippocampal‐sparing. Future studies should explore whether comorbid AD pathology underlies the atrophy patterns seen in DLB.